Plato's Pragmatism : Rethinking the Relationship Between Ethics and Epistemology - Baima, Nicholas R. (Taylor & Francis Group, 2020)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Translations and Abbreviations -- Prelude -- 1 The Alethic Interpretation -- 2 Summary -- 3 Methodology -- Notes -- Part I: Virtue, Veracity, and Noble Lies -- Chapter 1: Beneficial Falsehoods in the Republic : The Priority of the Practical -- 1.1 Genuine Falsehoods and Falsehood in Words -- 1.2 Reality and Matters of Fact -- 1.3 The Most Authoritative Things -- 1.3.1 Ethical Matters -- 1.3.2 The Forms -- 1.4 Ethical Commitments -- 1.5 The Priority of the Practical -- Notes -- Chapter 2: Ethical Commitments and Persuasion in the Laws -- 2.1 Preludes, Persuasion, and Medicine -- 2.2 Scholarly Impasse -- 2.3 On the Weakness of Moral Motivation -- 2.4 Religion for the Unsophisticated -- 2.5 Ignorance, Vice, and Motivation -- 2.6 Summary -- Notes -- Chapter 3: The Ring of Gyges and the Nature of Ethical Commitments -- 3.1 The Compatibility Thesis -- 3.2 Normative Objects and the Limiting Requirement -- 3.3 Intrinsic Valuing within a Eudaimonist Framework -- 3.4 The Importance of Ethical Commitments -- 3.5 Justified Lying and Ethical Commitments -- 3.6 Summary -- Notes -- Part II: Courage, Caution, and Faith -- Chapter 4: Charming Away the Fear of Death in the Phaedo -- 4.1 The Phaedo Anomaly -- 4.2 "The Best of Men" -- 4.3 The Phaedo Anomaly Redux -- 4.4 The Limits of Truth -- 4.5 Summary -- Notes -- Chapter 5: Better, Braver, and Less Idle: Faith and Inquiry in the Meno -- 5.1 Obstacles to Inquiry -- 5.2 Virtue as a Reason for Belief -- 5.3 Intellectual Courage -- 5.3.1 Courage -- 5.3.2 Courage vs. Recklessness -- 5.3.3 Against Abstinence -- 5.4 Summary -- Notes -- Chapter 6: Absurdity and Speciousness in the Protagoras and the Euthydemus -- 6.1 The Puzzle -- 6.1.1 Recommendation to the Young -- 6.1.2 Inquiry -- 6.2 Truthfulness and Absurdity -- 6.2.1 Intention.